The Effect of Property Rights and Audit Information Quality on Team Incentives for Inventory Reduction - Balakrishnan, Ramji; Nagarajan, Nandu J.; Sivaramakrishnan, K. (Management Science, 1998)
We analyze how limited contractibility and the informational quality of audits affect inventory levels and the optimality of individual versus team-based production. We use a two-period agency model in which contractibility is limited and agents meet a fixed delivery quota each period. A costly audit is triggered in any period if the delivery quota of output for the period is not met. We show that the informativeness of the audit plays a crucial role in resolving coordination problems between agents when they are organized as a team. When the audit is perfectly informative about agent productivity and inventory levels, team-based production is optimal. The team meets its quota even though, in equilibrium, the audit never takes place. If the audit is not perfectly informative about inventory levels, we show that team-based production typically induces agents to endogenously reduce inventory levels and could even result in agents adopting a zero-inventory policy. When the audit is completely uninformative, individual production is superior to team-based production.